JWST Observations of the Ring Nebula (NGC 6720). III. A Dusty Disk around Its Central Star - Raghvendra Sahai; Griet Van de Steene; Peter A. M. van Hoof; Albert Zijlstra; Kevin Volk; Harriet L. Dinerstein; Michael J. Barlow; Els Peeters; Arturo Manchado; Mikako Matsuura; Jan Cami; Nick L. J. Cox; et al. (The Astrophysical Journal)
The planetary nebula NGC 6720, also known as the “Ring Nebula,” is one of the most iconic examples of nearby planetary nebulae whose morphologies present a challenge to our theoretical understanding of the processes that govern the deaths of most stars in the Universe that evolve on a Hubble time. We present new imaging with JWST of the central star of this planetary nebula (CSPN) and its close vicinity, in the near-to-mid-IR wavelength range. We find the presence of a dust cloud around the CSPN, both from the spectral energy distribution at wavelengths ≳5 μ m as well as from radially extended emission in the 7.7, 10, and 11.3 μ m images. From the modeling of these data, we infer that the CSPN has a luminosity of 310 L _⊙ and is surrounded by a dust cloud with a size of ∼2600 au, consisting of relatively small amorphous silicate dust grains (radius ∼0.01 μ m) with a total mass of 1.9 × 10 ^−6 M _⊕ . However, our best-fit model shows a significant lack of extended emission at 7.7 μ m—we show that such emission can arise from a smaller (7.3 × 10 ^−7 M _⊕ ) but uncertain mass of (stochastically heated) ionized polycyclic aromatic hydrocarbon (PAHs). However, the same energetic radiation also rapidly destroys PAH molecules, suggesting that these are most likely being continuously replenished, via the outgassing of cometary bodies and/or the collisional grinding of planetesimals. We also find significant photometric variability of the central source that could be due to the presence of a close dwarf companion of mass ≤0.1 M _⊙ .